Enzymatic analysis of α-ketoglutaramate—A biomarker for hyperammonemia - Halámková, Lenka (2012)
Two enzymatic assays were developed for the analysis of α-ketoglutaramate (KGM)—an important biomarker of hepatic encephalopathy and other hyperammonemic diseases. In both procedures, KGM is first converted to α-ketoglutarate (KTG) via a reaction catalyzed by ω-amidase (AMD). In the first procedure, KTG generated in the AMD reaction initiates a biocatalytic cascade in which the concerted action of alanine transaminase and lactate dehydrogenase results in the oxidation of NADH. In the second procedure, KTG generated from KGM is reductively aminated, with the concomitant oxidation of NADH, in a reaction catalyzed by L-glutamic dehydrogenase. In both assays, the decrease in optical absorbance (λ=340 nm) corresponding to NADH oxidation is used to quantify concentrations of KGM. The two analytical procedures were applied to 50% (v/v) human serum diluted with aqueous solutions containing the assay components and spiked with concentrations of KGM estimated to be present in normal human plasma and in plasma from hyperammonemic patients. Since KTG is the product of AMD-catalyzed hydrolysis of KGM, in a separate study, this compound was used as a surrogate for KGM. Statistical analyses of samples mimicking the concentration of KGM assumed to be present in normal and pathological concentration ranges were performed. Both enzymatic assays for KGM were confirmed to discriminate between the predicted normal and pathophysiological concentrations of the analyte. The present study is the first step toward the development of a clinically useful probe for KGM analysis in biological fluids.